(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In the article problems of intrinsic vulnerability assessment of aquifers operating for drinking water supply of Gavar City are discussed. Investigation methods, hydrogeological conditions of western part of the Sevan basin, as well as intrinsic vulnerability of aquifers on borehole data are brought in the article. It has been established, that water-table aquifer is poorly protected, but the confined aquifer is protected.